PERAN APLIKASI WHATSAPP SEBAGAI MEDIA PEMBELAJARAN DALAM MATA KULIAH METODOLOGI PENELITIAN (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
Social media is the most popular service at the moment. Its users can communicate with each other, interact, share, network, and various other activities. Currently, one of the social media that can be used easily by students is WhatsApp. More effort is needed to find creative ways to increase students’ activity in learning. Looking the development of technology and the increasing number of users, the use of social media such as WhatsApp is very appropriate to be applied in the learning process. The use of WhatsApp in the learning process will give students the ability to get more information, lecturers, to be connected with study groups and other education systems with the same topics and problems, will make the learning process more interesting. This research was conducted to look the role of whatsApp as a leraning media in studying research methodology to increase student learning activities. The purposes of this research is to know to what extent knowing the media based on WhatsApp instant messaging application can be used to improve activity learning in studying research methodology. The data was analysed using descriptive statistical method by using percentage. There is 94 % of student improve their learning outcome in studying research methodology. The result of data analyzes shown there are significant effects of the role of WhatsApp as a learning media in studying research methodology to increase student learning activities.